2015
DOI: 10.1089/ars.2014.5917
|View full text |Cite
|
Sign up to set email alerts
|

Modes of Physiologic H2S Signaling in the Brain and Peripheral Tissues

Abstract: Significance: Hydrogen sulfide (H 2 S), once associated with rotten eggs and sewers, is now recognized as a gasotransmitter that is synthesized in vivo in a regulated fashion. This ancient gaseous molecule has been retained throughout evolution to perform various roles in different life forms. H 2 S modulates important signaling functions in diverse cellular processes ranging from regulation of blood pressure to redox homeostasis. Recent Advances: One of the modes by which H 2 S signals is by post-translationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 105 publications
(119 reference statements)
0
47
0
Order By: Relevance
“…To delineate the mechanism by which CO inhibits CSE, we first considered whether CO inhibits calmodulin, a calcium-dependent activator of CSE (12). CO might inhibit CSE activity by reducing the pool of intracellular calcium available to stimulate calmodulin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To delineate the mechanism by which CO inhibits CSE, we first considered whether CO inhibits calmodulin, a calcium-dependent activator of CSE (12). CO might inhibit CSE activity by reducing the pool of intracellular calcium available to stimulate calmodulin.…”
Section: Resultsmentioning
confidence: 99%
“…Emerging evidence suggests that CO suppresses H 2 S signaling by inhibiting the H 2 S-synthesizing enzymes cystathionine-γ-lyase (CSE) (7) and cystathionine β-synthase (CBS) (4, 6, 8, 9). CSE is the predominant source of H 2 S in peripheral tissues such as the carotid body (7, 10), whereas CBS is responsible for most of the H 2 S production in the brain (11, 12). It is believed that CO directly inhibits CBS by binding to its heme moiety (6, 8, 9).…”
Section: Introductionmentioning
confidence: 99%
“…Also, H2S is oxidized to polysulfides (H2Sn), that are more stable than H2S and in itself can act as signaling molecules. In fact, because of their oxidation state polysulfides are thought to be more potent to signal through sulfhydration than H2S [5,15,38].…”
Section: H2s Production and Biological Functionsmentioning
confidence: 99%
“…H2S also promote tumor growth by promoting angiogenesis and vasorelaxation [82]. Depletion of CBS can reverse H2S-mediated angiogenesis in colon cancer [83]. Taken together, these results indicate that CBS plays an important role in promoting angiogenesis and tumor growth.…”
Section: Cellular Metabolism and H2s Signalingmentioning
confidence: 99%
“…H2S stimulates both processes and causes a reduction in inflammatory response [114]. Exposure to H2S also rendered macrophages hyporesponsive to inflammatory stimuli such as bacterial endotoxin or TNF-α [83]. Recently, it was shown that annexin- A1 serves as a pro-resolution mediator and H2S treatment facilitates this process by translocating annexin-A1 from cytosol to plasma membrane [83].…”
Section: Inflammation and H2s Signalingmentioning
confidence: 99%